Carbon dots functionalized papers for high-throughput sensing of 4-chloroethcathinone and its analogues in crime sites. Issue 9 (11th September 2019) - Yen, Yao-Te; Lin, Yu-Syuan; Chen, Ting-Yueh; Chyueh, San-Chong; Chang, Huan-Tsung
Abstract : Sensitive and selective assays are demanded for quantitation of new psychoactive substances such as 4-chloroethcathinone that is a π-conjugated keto compound. Carbon dots (C-dots) prepared from L-arginine through a hydrothermal route have been used for quantitation of 4-chloroethcathinone in aqueous solution and on C-dot-functionalized papers (CDFPs). To prepare CDFPs, chromatography papers, each with a pattern of 8 × 12 circles (wells), are first fabricated through a solid-ink printing method and then the C-dots are coated into the wells. π-Conjugated keto or ester compounds induce photoluminescence quenching of C-dots through an electron transfer process. At pH 7.0, the CDFPs allow screening of abused drugs such as cocaine, heroin and cathinones. Because of poor solubility of heroin and cocaine at pH 11.0, the C-dot probe is selective for cathinones. The C-dots in aqueous solution and CDFPs at pH 11.0 allow quantitation of 4-chloroethcathinone down to 1.73 mM and 0.14 mM, respectively. Our sensing system consisting of a portable UV-lamp, a smartphone and a low-cost CDFP has been used to detect cathinones, cocaine and heroin at pH 7.0, showing its potential for screening of these drugs in crime sites.